Comparison of Cytotoxicity of Four Different Adhesive Materials Before and After Polymerisation - Cangul, Suzan; Adiguzel, Ozkan; Tekin, Samet (Quintessence Publishing Co Inc, 2020)
Introduction: The aim of this study was to make a quantitative comparison of the cytotoxic potentials of four different polymerised and unpolymerised self-etching adhesives which were newly used clinically. Materials and Methods: Cytotoxic effects of both polymerised and unpolymerised forms of all test adhesives were evaluated against L929 cell line using the MTT test. The activity for unpolymerised adhesives was assessed in different doses and incubation times manner. On the other hand, cytotoxicity of the polymerised adhesives prepared at different extraction times were evaluated as dependent on incubation times. Two-Way Variance Analysis and Bonferroni post-test was used for statistical evaluation. Results: There were statistically significant differences between the groups (p < 0.05). In general, it was shown that unpolymerised and polymerised forms of each of the test compounds exhibited a time-dependent cytotoxic effect. However, the effect on polymerised forms was found to be independent of the duration of the extraction, while the effect on the unpolymerised forms increased dose-dependently. It was also determined that the most cytotoxic material in the unpolymerised form was Dentsply and in the polymerised form was Tokuyama. Conclusions: Dentsply should be preferred over Tokuyama to be able to provide clinically long-lasting restorations.
Keywords: adhesive materials; cytotoxicity; polymerisation; MTT test